A Model of Manau Rattan Distribution Cost in Sumatra - Dewi, Nurlaela Kumala; Pradono, Pradono; Miharja, Miming; Yudoko, Gatot (International Journal of Supply Chain Management, 2017)
Currently, rattan raw material price is not stable because its price is influenced by the difficulties encountered in rattan raw materials distribution from the upstream to the downstream. Establishing a distribution model will help to improve Indonesian rattan distribution policy within the framework of the dynamic system. It also restores rattan market condition into the mechanism of rattan trading so that rattan businessmen will be more independent and be able to set their own trading system. It is expected that through this policy, they will experience a fairer and more competitive rivalry in this rattan industry.